Association between Streptococcus gallolyticus and colorectal cancer in Mansoura University hospitals. Issue 1 (1st January 2021) - Eldegla, Heba E.; Abdel-Wahhab, Mohamed; Moemen, Dalia
ABSTRACT: Streptococcus gallolyticus (S. gallolyticus) bacteria are associated with colorectal cancer and adenoma. About 25–80% of patients with S. bovis bacteremia have concomitant colorectal tumors. This case control study aimed to detect the prevalence of S. gallolyticus in colorectal cancer tissues of patients attending Gastrointestinal Surgery Center (GISC) for colonoscopy, determine the correlation with the endoscopic finding and identify risk factors for acquisition of S. gallolyticus . Case samples were colorectal cancer tissue, obtained from 48 colorectal cancer patients who performed colonoscopy before administration of chemotherapy, control samples were normal colonic tissue taken from 48 persons who performed colonoscopy for any reason other than colorectal cancer. For isolation and identification of S. gallolyticus, the samples were processed, seeded on bile esculin agar, suspected colonies were identified with Gram staining, catalase, and pyrolidonyl arylamindase test. Age was significantly older in cases compared to controls. Both gender and residence did not significantly differ between the study groups. Occupational contact with animals was significantly higher in cases compared to control. The prevalence of S. gallolyticus in colorectal cancer tissues was 35.4%. S. gallolyticus on the surface was positive in 64.6% of cases, versus only 18.8% of controls. On univariate analysis, diarrhea was a significant risk factor for having surface S. gallolyticus . No significant risk factors for colonizing S. gallolyticus in tissue were identified. The early detection of S. gallolyticus in cases of colorectal adenomas might be of high value in screening high risk groups for colorectal cancer.